Strategi Guru BK Mengoptimalkan Layanan Dengan Keterbatasan Sarana & Prasarana di SMPN 3 Tigo Nagari - Julita, Irma; N, Neviyarni; Syukur, Yarmis (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the strategies of Guidance and Counseling (BK) teachers in optimizing services at SMPN 3 Tigo Nagari, which faces limited facilities and infrastructure. The school does not have individual or group counseling rooms and does not provide standard assessment instruments such as General AUM, PTSDL AUM, and psychological tests. Using a descriptive qualitative approach, data was obtained through interviews with BK teachers, observations of BK facilities, and field documentation. Analysis was conducted through data reduction, presentation, and conclusion drawing using the Miles, Huberman, and Saldaña model. The results indicate that BK services continue to operate through four main service components, despite very limited facilities. BK teachers implement five strategies: the use of digital technology, the use of the living room as a counseling room, the implementation of classroom services, collaboration with homeroom teachers and subject teachers, and the use of simple media. The study concludes that BK teachers' creativity and adaptability play a significant role in maintaining service effectiveness in conditions of limited facilities.